The Effect of Environmental Performance, Profitability, and Institutional Ownership on Carbon Emission Disclosure - Sang Ayu Nyoman Rina Puspita; I Gusti Ayu Nyoman Budiasih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Climate change driven by global warming has prompted companies to enhance transparency regarding the environmental impacts of their operational activities, particularly in the disclosure of carbon emissions. Such disclosure is essential to address stakeholder demands and to gain social legitimacy, in accordance with stakeholder theory, which serves as the foundation of this study. This research aims to empirically examine the effect of environmental performance, profitability, and institutional ownership on carbon emission disclosure among non-financial companies listed on the Indonesia Stock Exchange. The population of this study comprises non-financial companies listed on the Indonesia Stock Exchange from 2020 to 2023. The sample was selected using a purposive sampling technique, resulting in 332 observations from 115 companies. The data analysis method employed is multiple linear regression analysis. The results reveal that environmental performance has a positive effect on carbon emission disclosure, indicating that the better the company’s environmental performance, the higher the level of carbon emission disclosure. Profitability and institutional ownership, however, have no significant effect on carbon emission disclosure.